Chitosan Nanoparticles as Seed Priming Agents to Alleviate Salinity Stress in Rice (Oryza sativa L.) Seedlings - Akanksha T. Soni; James E. Rookes; Sagar S. Arya (Polysaccharides, 2023)
Nanoparticle-based seed priming has opened new avenues in crop science due to their plant growth promoting potential. Similarly, biopolymers such as chitosan (CS) are widely studied as seed priming agents due to the biodegradable and biocompatible nature, ability to enhance germination percentage and overall seedling health. Therefore, priming with chitosan nanoparticles (CNPs) is a promising tool to enhance overall plant health. Here, we studied the effect of nanopriming with CNPs or CS (50 µg/mL) on morphological, physiological, and biochemical parameters of rice seedlings, grown in salinity stress conditions NaCl (0–250 mM). CNPs were synthesized using an ionic gelation method and characterized by scanning electron microscopy (50–100 nm), zeta potential analyser (Particle size distribution–373.5 ± 3.7 nm; polydispersity index- > 0.4; zeta potential–45.3 ± 2.5 mV) and profilometry (300–1500 nm hydrodynamic height). Morphological, physiological, and biochemical responses of rice seedlings grown from seeds primed with either CNPs or CS showed a positive effect on germination, seedling vigour, biochemical and antioxidant responses. Seeds primed with CNPs and CS demonstrated significantly higher germination potential and seedling vigour compared to control hydro-primed seeds when grown under increasing NaCl concentrations. These outcomes highlight that CNPs and CS can be used as potential seed priming agents to alleviate salinity stress in rice seedlings. However, further studies are warranted to understand the effect of CNPs and CS seed priming on the overall growth and development of rice plants as well as rice yield.